Mouse Spexin: (III) Differential Regulation by Glucose and Insulin in Glandular Stomach and Functional Implication in Feeding Control - Chen, Yuan; He, Mulan; Lei, Martina M. L.; Ko, Wendy K. W.; Lin, Chengyuan; Bian, Zhaoxiang; Wong, Anderson O. L. (Frontiers in Endocrinology, 2021)
Spexin (SPX), a neuropeptide with diverse functions, is a novel satiety factor in fish models and its role in feeding control has been recently confirmed in mammals. In mouse, food intake was shown to trigger SPX expression in glandular stomach with parallel rise in serum SPX and these SPX signals could inhibit feeding via central actions within the hypothalamus. However, the mechanisms for SPX regulation by food intake are still unclear. To examine the role of insulin signal caused by glucose uptake in SPX regulation, the mice were IP injected with glucose and insulin, respectively. In this case, serum SPX was elevated by glucose but not altered by insulin. Meanwhile, SPX transcript expression in the glandular stomach was up-regulated by glucose but the opposite was true for insulin treatment. Using in situ hybridization, the differential effects on SPX gene expression were located in the gastric mucosa of glandular stomach. Co-injection experiments also revealed that glucose stimulation on serum SPX and SPX mRNA expressed in glandular stomach could be blocked by insulin. In gastric mucosal cells prepared from glandular stomach, the opposite effects on SPX transcript expression by glucose and insulin could still be noted with similar blockade of the stimulatory effects of glucose by insulin. In this cell model, SPX gene expression induced by glucose was mediated by glucose uptake via GLUT, ATP synthesis by glycolysis/respiratory chain, and subsequent modulation of KATP channel activity, but the voltage-sensitive Ca2+ channels were not involved. The corresponding inhibition by insulin, however, was mediated by PI3K/Akt, MEK1/2/ERK1/2 and P38 MAPK cascades coupled to insulin receptor but not IGF-1 receptor. Apparently, glucose uptake in mice can induce SPX expression in the glandular stomach through ATP synthesis via glucose metabolism and subsequent modification of KATP channel activity, which may contribute to SPX release into circulation to act as the satiety signal after food intake. The insulin rise caused by glucose uptake, presumably originated from the pancreas, may serve as a negative feedback to inhibit the SPX response by activating MAPK and PI3K/Akt pathways in the stomach.